Social Immersion for Women After Repair for Obstetric Fistula: An Experience in Guinea - Delamou, Alexandre; Douno, Moussa; Bouédouno, Patrice; Millimono, Sita; Barry, Thierno Hamidou; Tripathi, Vandana; Diallo, Moustapha (Frontiers in Global Women's Health, 2021)
Background: Reintegration of women after repair of their female genital fistula remains a challenge. The objective of this study was to document the medical pathway and the reintegration process of women through the “social immersion” program of EngenderHealth in Kissidougou and Labé (Guinea). Methods: This was a qualitative descriptive study with 55 participants, including women seeking fistula care and stakeholders involved in the social immersion for repaired women in Kissidougou and Labé. The study included collecting demographic and clinical data of women, interviews with women before and after surgery, after social immersion, and 3 months post-discharge. Municipal officials, health providers, and members of host families were also interviewed. The study protocol was approved by the Guinea National Ethics Committee for Health Research. Results: The study confirmed that obstetric fistula still occurs among women living in rural and underserved areas. Most women attended at least two to five antenatal care visits, but nine over 10 reported a tragic experience of child loss associated with the occurrence of fistula. Most of them received support from their husband/partner during referral after the obstructed labor and later in the search for treatment. Women and stakeholders reported a good experience of surgery and social immersion in both Kissidougou and Labé. About 3 months after discharge, women who were continent reported being happy with their new life compared to women discharged with repair failure and residual incontinence. Conclusion: The study found the positive impacts of social immersion on the quality of life of women after fistula repair, particularly for those women who had a successful repair. The approach can be included in fistula care programs, either through direct provision or through referral to programs that can provide this service.